The taxonomic status of the Italian Sparrow — Passer italiae (Vieillot 1817): Speciation by stabilised hybridisation? A critical analysis - Töpfer, Till (Zootaxa, 2006)
Since its description the taxonomic status of the Italian Sparrow Passer italiae (Vieillot 1817) has changed repeatedly according to the speciation concepts applied. Due to external similarities with hybrid sparrow individuals the hypothesis that italiae is a stabilised hybrid form between Passer domesticus (L. 1758) and P. hispaniolensis (Temm. 1820) has deeply influenced the discussion although some authors do not even accept hybrid forms as taxa. Based upon a comprehensive review of the literature it is shown that the postulation of a hybrid origin of italiae is inadmissible, being based on a methodologically circular argument. There is no convincing proof of stabilised hybridisation. Therefore Passer italiae is a real taxon and not a hybrid form. Applying the Biospecies Concept according to current knowledge of distributional facts and the lack of reproductive isolation between italiae and hispaniolensis I argue that these two forms are conspecific. Passer domesticus is not conspecific with them. According to the rules of zoological nomenclature the taxa have to be designated as Passer italiae italiae (Vieillot 1817) and Passer italiae hispaniolensis (Temminck 1820).